Need to create by law of, a program of guidance, preparation and training of the worker to retire - Barreda Guerra, Juan Manuel (2018)
Retirement represents for the worker the satisfaction of having fulfilled his mission in life. The retirement age of the worker in the law, has costumbristas, historical, biological and universal components. The law does not consult the worker if he feels able to continue in his work even when the law tells him to retire, the law does not contemplate the type of work that the worker performs, as is the case of performance in intellectual activities, Innovative, legislative, organizational, and activities in which the worker performs with high productivity yields despite being according to law at retirement age. These and other situations demand the existence of a program of orientation, preparation and training to the worker. The greatest emphasis that must be placed on this type of proposal is in psychological preparation and training the worker for their independent performance as it is in developed countries with high social responsibility, the inexistence of this program in our country constitutes a huge social vacuum.